The Influence of Triad Selection on the Preference Scaling Results - Zaborski, Artur (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
In the method of triads for a set of n objects all three element sets of objects are presented to the respondents. A respondent is asked to pick out the most similar and the least similar pair. The method of triads, despite its numerous advantages, is rarely used in practice. The number of triads is a cubic function of the number of objects and increases very rapidly with the number of objects. The aim of the study is to indicate the possibility of scaling preferences based on the reduced number of triads. It has also been examined whether the change of reduced set of triads influences the results of the scaling. The results of the analysis are illustrated by an empirical example in which preference scaling for different sets of triads was performed with the use of TRISOSCAL program.